SOCIAL REPRESENTATION OF PHYSICAL AND PSYCHOLOGICAL VIOLENCE AND ABANDONMENT FROM THE PERSPECTIVE OF ELDERLY PEOPLE - Chagas, Ana Luiza Cabral da Cunha de Almeida; Cunha, Maria Luísa Cabral da; Bezerra, Kalyne Araújo; Santos, José Darlan da Silva; Marcolino, Emanuella de Castro; Rodrigues, Renata Clemente dos Santos (Cogitare Enfermagem, 2024)
Objective: To understand the perception of the elderly regarding physical violence, psychological violence, and abandonment. Method: A cross-sectional, descriptive study with a qualitative approach based on the Theory of Social Representations. Developed with elderly people registered at a Basic Health Unit in Campina Grande-PB, Brazil, between April and May 2022 through data collection based on a semi-structured interview. Results: 14 elderly people participated, 86% (12) of whom were female and aged between 61 and 83. The results showed that the elderly are aware of the typologies discussed, with psychological violence being the least understood by them; about abandonment, the elderly described it as loneliness and asylum. Conclusion: This study allowed the concept of violence to be understood by the elderly, which contributes substantially to health actions, especially by nursing professionals in the identification and assertive intervention.